Identification and Characterization of a Predominant Hydrophobin in the Edible Mushroom Grifola frondosa - Bo Song; Wenjun Wang; Chunhui Jia; Zhiqiang Han; Jiyuan Yang; Jiuxia Yang; Zhenzhou Wu; Haijin Xu; Mingqiang Qiao (Journal of Fungi, 2023)
Hydrophobins (HFBs) are a group of small, secreted amphipathic proteins of fungi with multiple physiological functions and potential commercial applications. In this study, HFB genes of the edible mushroom, Grifola frondosa, were systematically identified and characterized, and their transcriptional profiles during fungal development were determined. In total, 19 typical class I HFB genes were discovered and bioinformatically analyzed. Gene expression profile examination showed that Gf.hyd9954 was particularly highly upregulated during primordia formation, suggesting its major role as the predominant HFB in the lifecycle of G. frondosa. The wettability alteration profile and the surface modification ability of recombinant rGf.hyd9954 were greater than for the Grifola HFB HGFII-his. rGf.hyd9954 was also demonstrated to form the typical class I HFB characteristic-rodlet bundles. In addition, rGf.hyd9954 was shown to possess nanoparticle characteristics and emulsification activities. This research sheds light on the regulation of fungal development and its association with the expression of HFB genes.